Cenicriviroc for the treatment of COVID-19: first interim results of a randomised, placebo-controlled, investigator-initiated, double-blind phase II trial. (March 2023) - Kurth, Florian; Helbig, Elisa T.; Lippert, Lena J.; Thibeault, Charlotte; Barbone, Gianluca; Eckart, Marius A.; Kluge, Martin; Puengel, Tobias; Demir, Münevver; Röhle, Robert; Keller, Theresa; Ruwwe-Glösenkamp, Christoph; et al.
Highlights: A pathophysiologic rationale supports chemokine receptor (CCR) inhibition in COVID-19 This randomised controlled human trial assessed CCR inhibitor CVC in COVID-19 Data document efficient CCR2/CCR5 inhibition through CCL2/4 elevation in CVC treated patients. CVC was safe and well tolerated by COVID-19 patients. Abstract: Objectives: C-C-chemokine receptors (CCRs) are expressed on a variety of immune cells and play an important role in many immune processes, particularly leukocyte migration. Comprehensive preclinical research demonstrated CCR2/CCR5-dependent pathways as pivotal for the pathophysiology of severe COVID-19. Here we report human data on use of a chemokine receptor inhibitor in patients with COVID-19. Methods: Interim results of a 2:1 randomised, placebo-controlled, investigator-initiated trial on the CCR2/CCR5-inhibitor Cenicriviroc (CVC) 150 mg BID orally for 28 d in hospitalised patients with moderate to severe COVID-19 are reported. The primary endpoint is the subject's responder status defined by achieving grade 1 or 2 on the 7-point ordinal scale of clinical improvement on day 15. Results: Of the 30 patients randomised, 18 were assigned to receive CVC and 12 to placebo. Efficient CCR2- and CCR5 inhibition was demonstrated through CCL2 and CCL4 elevation in CVC-treated patients (485% and 80% increase on day 3 compared to the baseline, respectively). In the modified intention-to-treat population, 82.4% of patients (14/17) in the CVC group met the primary endpoint, as did 91.7% (11/12) in the placebo group (OR = 0.5, 95% CI = 0.04–3.41). One patient treated with CVC died of progressive acute respiratory distress syndrome, and the remaining had a favourable outcome. Overall, treatment with CVC was well tolerated, with most adverse events being grade I or II and resolving spontaneously. Conclusions: Our interim analysis provides proof-of-concept data on CVC for COVID-19 patients as an intervention to inhibit CCR2/CCR5. Further studies are warranted to assess its clinical efficacy.